2022
DOI: 10.3390/nu14173563
|View full text |Cite
|
Sign up to set email alerts
|

Updated Information of the Effects of (Poly)phenols against Type-2 Diabetes Mellitus in Humans: Reinforcing the Recommendations for Future Research

Abstract: (Poly)phenols have anti-diabetic properties that are mediated through the regulation of the main biomarkers associated with type 2 diabetes mellitus (T2DM) (fasting plasma glucose (FPG), glycated hemoglobin (HbA1c), insulin resistance (IR)), as well as the modulation of other metabolic, inflammatory and oxidative stress pathways. A wide range of human and pre-clinical studies supports these effects for different plant products containing mixed (poly)phenols (e.g., berries, cocoa, tea) and for some single compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…A wide range of human intervention trials and preclinical studies have also shown the possible antidiabetic properties of polyphenols, but evidence is still limited and inconsistent (Menezes et al, 2022).…”
Section: Antidiabetic Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of human intervention trials and preclinical studies have also shown the possible antidiabetic properties of polyphenols, but evidence is still limited and inconsistent (Menezes et al, 2022).…”
Section: Antidiabetic Effectmentioning
confidence: 99%
“…For instance, prospective analysis in the context of the PREDIMED-Plus trial conducted by Menezes et al (2022) showed that a diet with higher polyphenols lowered the levels of glucose and HbA1c after 1 year in a senior population with T2DM or are at high risk of developing T2DM. In another study carried out by Grabež et al (2022), they observed that polyphenols extracted from pomegranate peel decreased oxidative stress biomarkers such as O −2 , NO −2 , TBARS, inflammatory factors (IL-6, TNF-α, hsCRP), and homocysteine in overweight patients with T2DM.…”
Section: Antidiabetic Effectmentioning
confidence: 99%
“…Resveratrol, curcumin, genistein, quercetin, phloretin, caffeic acid, and epigallocatechin gallate—just to name a few—are remarkably popular natural compounds that, together with their glycosides, make up some of the most vastly studied sets of molecules for diabetes. In spite of the high amount of in vitro cell-based assays claiming promising (poly)phenol-induced antidiabetic effects, those results translate very poorly into successful outcomes in clinical studies [ 9 ]. Indeed, the antidiabetic effects of natural (poly)phenols in human subjects are often small or non-significant, with high variability between studies [ 9 ].…”
mentioning
confidence: 99%
“…In spite of the high amount of in vitro cell-based assays claiming promising (poly)phenol-induced antidiabetic effects, those results translate very poorly into successful outcomes in clinical studies [ 9 ]. Indeed, the antidiabetic effects of natural (poly)phenols in human subjects are often small or non-significant, with high variability between studies [ 9 ]. Overall, the existing data has been found to be rather limited and even contradictory, highly contrasting with lab bench research.…”
mentioning
confidence: 99%
See 1 more Smart Citation